Implementation of the Notary’s Obligation to Read the Deed Before the Appearing Parties in Banda Aceh. - Cut Riska Yulanda; Ilyas Ilyas; Zahratul Idami (International Journal of Law and Society, 2026)
Law Number 2 of 2014 concerning the Office of Notary requires notaries to read deeds before the appearing parties in order to ensure legal certainty, guarantee that the parties understand the contents of the deed, and prevent disputes in the future. Issues concerning the failure to fulfill this obligation are reflected in the Decision of the Jantho District Court Number 7/Pdt.G/2024/PN Jth, which indicated allegations that the deed was not read directly before the signing process took place. This condition demonstrates that the reading of a deed is not merely an administrative formality, but an essential element in maintaining the validity of an authentic deed and public trust in the notarial profession. This study aims to analyze the legal consequences, the forms of notarial liability based on the Law on the Office of Notary and the Civil Code, as well as the legal facts contained in the court decision. This research employed an empirical juridical method with a qualitative approach through interviews and library research. The results of the study indicate that the obligation to read deeds has not been fully implemented, causing deeds to potentially suffer formal defects, lose their authentic nature, and degrade into private deeds with weaker evidentiary value, while also giving rise to administrative and civil liability for notaries. This study suggests that notaries should read deeds thoroughly, clearly, and systematically to ensure that the parties fully understand the contents and legal consequences of the deed executed.